1998
DOI: 10.1103/physreve.57.4535
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous magnetization in dipolar ferromagnetic liquids

Abstract: At high densities fluids of strongly dipolar spherical particles exhibit spontaneous long-ranged orientational order. Typically, due to demagnetization effects induced by the long range of the dipolar interactions, the magnetization structure is spatially inhomogeneous and depends on the shape of the sample. We determine this structure for a cubic sample by the free minimization of an appropriate microscopic density functional using simulated annealing. We find a vortex structure resembling four domains separa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Conversely, the numerical simulation of dipole systems [1,2] indicates that dipole-dipole interac tions may lead to the occurrence of a ferromagnetic phase in the form of a domain structure with nonuni form magnetization. The same results were obtained analytically in [3,4], and in [5] ferromagnetic fluctua tions were observed in a magnetic colloid with iron nitride particles. On the other hand, Pshenichnikov et al [6,7], having analyzed published data and their own magnetic measurement data for different ferro colloids, argue that there is no reason to expect a spon taneous transition to a magnetically ordered state in such systems.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Conversely, the numerical simulation of dipole systems [1,2] indicates that dipole-dipole interac tions may lead to the occurrence of a ferromagnetic phase in the form of a domain structure with nonuni form magnetization. The same results were obtained analytically in [3,4], and in [5] ferromagnetic fluctua tions were observed in a magnetic colloid with iron nitride particles. On the other hand, Pshenichnikov et al [6,7], having analyzed published data and their own magnetic measurement data for different ferro colloids, argue that there is no reason to expect a spon taneous transition to a magnetically ordered state in such systems.…”
Section: Introductionsupporting
confidence: 83%
“…The possibility of long range magnetic ordering in a system of single domain colloid particles has been considered in a number of works [1][2][3][4][5][6][7][8], but this issue remains poorly understood. Theoretically [9], such ordering in an ensemble of particles experiencing only magnetic dipole-dipole interactions seems unfeasi ble.…”
Section: Introductionmentioning
confidence: 99%
“…Choosing this somewhat minimalistic model, which lacks any dispersive interactions or asymmetric steric interactions due to different sizes of the spheres, thus permits us to study directly the influence of dipolar interactions on the mixture's phase behavior. In fact, recent research on onecomponent DHS fluids (and related model systems) has demonstrated that the long-range and highly anisotropic character of dipolar interactions yields new, unexpected phase behavior [10][11][12][13][14], including the possibility of spontaneous polarization in dense, strongly coupled DHS fluids [15][16][17][18][19][20][21][22]. In view of these findings, central topics of the present study are the appearance of such ferroelectric phases in twocomponent fluids, and their interplay with demixing transitions expected to take place for highly asymmetric mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Due to convergence considerations, the spatial integration has to be performed carefully for such an expression. In a series of very interesting and thought provoking papers, Groh and Dietrich [87][88][89][90][91][92] have considered this problem in detail, and have concluded that the shape of the fluid sample has to be considered explicitly with this type of integral. By performing the spatial integration in an uniaxial ellipsoidal sample with axial ratio (k), one obtains the following result:…”
Section: B Dipolar Gay-berne Systemmentioning
confidence: 99%
“…From a careful and rigorous treatment of the electromagnetic properties of systems with dipolar interactions, Groh and Dietrich [87][88][89][90][91][92] have used a densityfunctional treatment with the correct second virial coefficient of the long-range dipolar interaction to show that the stability of the polar phases is governed both by the shape of the sample and the nature of the dielectric medium surrounding it. Their calculations for the spherical Stockmayer system [87][88][89][90]92 indicated that the system exhibits a ferroelectric fluid phase, although for small values of the dipole moment the polar fluid phase was shown to be preempted by a freezing transition. 90 The numerous other theoretical studies of phase transitions in dipolar spherical particles are reviewed in Ref.…”
Section: Introductionmentioning
confidence: 99%